2008
DOI: 10.1029/2008gc002091
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and microbiological fingerprinting of airborne dust that fell in Canberra, Australia, in October 2002

Abstract: [1] During the night of 22-23 October 2002, a large amount of airborne dust fell with rain over Canberra, located some 200 km from Australia's east coast, and at an average altitude of 650 m. It is estimated that during that night about 6 g m À2 of aeolian dust fell. We have conducted a vast number of analyses to ''fingerprint'' some of the dust and used the following techniques: grain size analysis; scanning electron microscope imagery; major, trace, and rare earth elemental, plus Sr and Nd isotopic analyses;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 88 publications
0
38
2
1
Order By: Relevance
“…Van Mooy and Fredricks, 2010). Dust additions could also represent a major source of PC, as observed in airborne particles in Australia, which were loaded with roughly 0.43 mg PC g −1 (De Deckker et al, 2008); however, the delayed increases in PC concentration on day 6 in treatment mesocosms (Figures 6, 7) are not consistent with this interpretation. The most abundant alkyl chains of PC in the experimental mesocosms (i.e., C 28:0 , C 29:1 , and C 31:1 ) were composed of a mix of C 14 , C 15 , C 16 fatty acids, and thus suggestive of a bacterial source, consistent with the assignment of PC to heterotrophic bacteria in the oligotrophic Sargasso Sea (Popendorf et al, 2011a; Table 4).…”
Section: Ipl Taxonomic Source Indicationscontrasting
confidence: 51%
See 1 more Smart Citation
“…Van Mooy and Fredricks, 2010). Dust additions could also represent a major source of PC, as observed in airborne particles in Australia, which were loaded with roughly 0.43 mg PC g −1 (De Deckker et al, 2008); however, the delayed increases in PC concentration on day 6 in treatment mesocosms (Figures 6, 7) are not consistent with this interpretation. The most abundant alkyl chains of PC in the experimental mesocosms (i.e., C 28:0 , C 29:1 , and C 31:1 ) were composed of a mix of C 14 , C 15 , C 16 fatty acids, and thus suggestive of a bacterial source, consistent with the assignment of PC to heterotrophic bacteria in the oligotrophic Sargasso Sea (Popendorf et al, 2011a; Table 4).…”
Section: Ipl Taxonomic Source Indicationscontrasting
confidence: 51%
“…The relatively enhanced availability of phosphorus in SD mesocosms could thus explain the significantly higher additions of PC in on day 6 (p < 0.04; Figures 6, 7). The delayed and significant increases in PC concentration in treatment mesocosms (Figure 6) is suggestive of autochthonous production rather than leaching from the amended dust (e.g., De Deckker et al, 2008). Given the capacity for SQ to substitute phospholipids , the net removal of SQ on day 3 in the SD treatments vs. net production in the A treatments (cf.…”
Section: Ipl Signatures Of Nutrient Turnovermentioning
confidence: 99%
“…Previous studies have shown that dust has a relatively unimodal grain size distribution with a peak value of approximately 40 μm and a secondary shoulder at approximately 100 μm. The coarsegrained shoulder could be due to platy minerals, which have aerodynamic behavior similar to fine-grained spherical particles (Stuut et al 2005;De Dekker et al 2008. Because fine-grained particles (mainly <63 μm) can be easily transported by wind from the source region to the CLP or to the North Pacific Ocean (Pye 1989;Rea 1994;Sun et al 2013), relatively fine-grained samples were collected for this study mainly from desert margins, dried riverbeds, or small hydrocephalus depressions within Gobi/sandy deserts, and alluvial fans at spacings of 50 to 100 km (Sun et al 2013).…”
Section: Geological Setting and Samplingmentioning
confidence: 99%
“…Bacterial assessments of desert dust have been performed in a range of locations from the Caribbean (Griffin et al 2001) to Korea (Hua et al 2007) and Australia (De Deckker et al 2008;Lim et al 2011;De Deckker et al 2014). Several studies based on culture-dependent methods have found that there are strong links between dust sources in the Sahara and sinks in the Caribbean and Mediterranean (Griffin et al 2003;Kellogg et al 2004;Griffin et al 2007).…”
mentioning
confidence: 98%
“…A decade-long drought in Australia resulted in an increase in dust transport, characterized by major dust storms in 2002(McTainsh et al 2005 and 2009 (Leys et al 2011) which affected a large proportion of the Australian population living along the east coast of the continent.…”
mentioning
confidence: 99%